Connecting short and long time dynamics in hard-sphere-like colloidal glasses. Issue 3 (1st December 2014) - Pastore, Raffaele; Pica Ciamarra, Massimo; Pesce, Giuseppe; Sasso, Antonio
Abstract : We connect the intermittent single particle motion and the macroscopic dynamics in experiments on colloidal glasses. Abstract : Glass-forming materials are characterized by an intermittent motion at the microscopic scale. Particles spend most of their time rattling within the cages formed by their neighbors, and seldom jump to a different cage. In molecular glass formers the temperature dependence of the jump features, such as the average caging time and jump length, characterizes the relaxation processes and allows for a short-time prediction of the diffusivity. Here we experimentally investigate the cage-jump motion of a two-dimensional hard-sphere-like colloidal suspension, where the volume fraction is the relevant parameter controlling the slowing down of the dynamics. We characterize the volume fraction dependence of the cage-jump features and show that, as in molecular systems, they allow for a short time prediction of the diffusivity.